A critical review of food safety legislation and policy applicable to products of animal origin in South Africa - Molefe, S.M.; McCrindle, C.M.E.; Botha, C.J.; Makita, K.; Grace, Delia (2011)
In South Africa, safety of animal derived food is fragmented, which complicates implementation at national, provincial and local level. Different aspects fall under the Departments of Health (DOH), Department of Agriculture, Forestry and Fisheries (DAFF), the Department of Trade and Industry (DTI)’s National Regulator for Compulsory Specifications (NRCS) and the South African Bureau of Standards (SABS). There are also a number of non-governmental stakeholders and role players involved. At international level these include the FAO, WHO, OIE and Codex. At national level they include SANAS, SABS, ISO and the private sector standards used by producers and processors of animal derived food. At local level there are provincial and municipal regulations for implementation of National directives, as well as private standards of supermarkets, butchers, dairies and other retailers of animal derived foods. As a result, lines of responsibility are not always well understood as they sometimes overlap or apply differently to different situations. Participatory risk analysis was done to assess the existing South African regulatory framework for key variables in food safety, against national and international FAO/ WHO/ OIE and Codex benchmark standards. Four working groups of eight key informants performed a gap analysis and defined actions and steps to remedy the limitations that currentlyexist in the registration of veterinary medicines and pesticides in animal feeds, animal health, laboratory capacity, surveillance and monitoring of animal diseases and both microbiological and chemical residues in animal source foodstuffs.This paper will describe and critically review the relevant legislation and regulations as well as their implementation, highlighting discrepancies and overlaps.